SPOTLIGHT ON THE HISTORY OF ANCIENT EGYPTIAN MEDICINE. - Eltorai, Ibrahim M. ([Place of publication not identified] : CRC PRESS, 2019)
This unique volume provides the reader with an outline of ancient Egyptian civilization, history and culture. It reviews the ancient Egyptian understanding of human health and disease, medical and herbal treatments for various conditions based on primary sources found in ancient papyri. The reader will also gain an insight into the influence of ancient Egyptian medical knowledge on later civilizations including ancient Greek and Islamic scholars in the middle ages. There are two chapters that focus on the ancient Egyptian understanding and treatments of cardiovascular disease as well as a description of herbal medicines used by medical practitioners and pharmacologists. Key Features: Describes influence of ancient Egyptian medical and pharmaceutical knowledge of subsequent civilizations Explores ancient Egyptian pharmacology and herbal medicine Review of the most significant ancient Egyptian papyri documenting medical knowledge and practice Concise overview of ancient Egyptian history, culture, medical knowledge Summary of ancient Egyptian understanding of cardiovascular diseases and treatments
Chapter 12 Clinical Aspects of Cardiovascular Diseases in Ancient Egypt (From the Ebers Papyrus: The Vascular Text)The Role of the Heart in Egyptian Thought; Chapter 13 Paleopathology of Cardiovascular Diseases and Pathogenesis with Analysis; Pathogenesis of Cardiovascular Diseases in Ancient Egypt; Chapter 14 Ancient Egyptian Pharmacology; Ancient Egyptian Medicines Used by Avicenna; Chapter 15 Tribute to the Scribe; References; Appendix: Book Reviews
OCLC-licensed vendor bibliographic record.
Keywords: Medicine, Egyptian; MEDICAL / General; MEDICAL / Administration; MEDICAL / Pharmacology